Ly6E on tumor cells impairs anti-tumor T-cell responses: a novel mechanism of tumor-induced immune exclusion - Lan Hailin; Chen Yiting; Wu Yue; Li Lijun; Zhang Renlu; Chen Yunhan; Zhu Yanyang; Zhang Qiuyu (Cancer Immunology, Immunotherapy)
Abstract Background Lymphocyte antigen 6 complex, locus E (Ly6E) has been initially demonstrated to involve in T cell activity and impair viral infectivity. Recently, high expression levels of Ly6E have been reported in tumor microenvironment (TME) of various types of cancers. However, the immunoregulatory mechanism of Ly6E manipulating TME remains unknown. Methods TCGA database and Kaplan–Meier plotter database were used to evaluate the correlation between Ly6E expression levels and cancer patient survival. After analyzing Ly6E expression levels in human breast cancer tissues and tumor cell lines, we generated Ly6E knockout (KO) and overexpression (OE) mouse cell lines. Cell proliferation ability in vitro and the ability of growth and metastasis in mouse tumor models were compared between KO/OE and wild-type tumor cells. On day 7 after tumor implantation, tumor tissues were separated for flow cytometric assay, bulk RNA sequencing and single-cell RNA sequencing (ScRNA-seq). The role of Ly6E-expressing tumor cell on macrophage was analyzed in vitro. Results Our result surprisingly found that high Ly6E expression levels were associated with CD8+ T cell exclusion in tumor tissues and resistance to immunotherapy. Our data showed that knockout of Ly6E in tumor cells prompts tumor regression and inhibits tumor metastases, and Ly6E-OE tumor cells vice versa. The enhanced anti-tumor effect of Ly6E knockout in tumor cells was dependent on T cell response and formed long-lasting memory. The increase in the CD8+ T-cell infiltration into the tumor islet of Ly6E-KO tumors confirmed the role of Ly6E on T cell exclusion. ScRNA-seq analysis showed that M2 macrophages are particularly abundant in the Ly6E-expressing tumor tissues, especially M2-4 macrophage cluster identified by high levels of Arg-1, indicates that Ly6E-expressing tumor cells might restrict T cell infiltration via M2 macrophages. Moreover, in vitro assay showed that cell culture media derived from Ly6E-positive tumor cells promoted macrophage migration and M2 polarization. Conclusion Our study illuminated that Ly6E-expressing tumor cells facilitated the accumulation of M2 macrophages in TME, which contributes to CD8+ T cell exclusion and provides new insights for improving efficacy of cancer immunotherapy.